Antitumor effects of 3‐bromoascochlorin on small cell lung cancer via inhibiting MAPK pathway. (1st August 2021) - Zhang, Zhenhua; Zhang, Yidi; Yang, Chunju; Wang, Qianyu; Wang, Hong; Zhang, Yanting; Deng, Wenbin; Nie, Yichu; Liu, Yonghong; Luo, Xiaowei; Huang, Jie; Wang, Junjian
Abstract: Small cell lung cancer (SCLC) was defined as a recalcitrant cancer, and novel therapies are urgently needed. Marine natural products (MNPs) may bring continuing hope for treatment of SCLC. In this study, 3‐bromoascochlorin (BAS), an MNP isolated from the coral‐derived fungus Acremonium sclerotigenum GXIMD 02501, was primarily screened out with antiproliferative activity towards SCLC cell lines. Then western blot analysis (WB) and flow cytometry were conducted, and we found BAS could induce the apoptosis of H446 and H69AR cells. Besides, BAS could suppress the invasion and migration of H446. In an SCLC xenograft mice model, BAS inhibited the growth of tumor without affecting the body weight of mice. Finally, the underlying mechanisms were preliminarily explored. According to the results of RNA‐seq, reverse transcription‐quantitative polymerase chain reaction, and WB, our results revealed that BAS exerted antitumor activity via inhibiting mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinases (ERK) pathway. Collectively, these results indicated that BAS can be used as a promising compound for the treatment of human SCLC.